Free Radicals Scavenging Activities of Low Molecular Weight Sodium Alginate (LMWSA) from Sargassum polycystum, Produced by Thermal Treatment - Yudiati, Ervia; Pringgenies, Delianis; Djunaedi, Ali; Arifin, Zaenal; Sudaryono, Agung (Indonesian Aquaculture Society (MAI), 2018)
In this study, the effects of alginate from Sargassum polycystum molecular reduction by thermal heating on DPPH anti radical scavenging activity were investigated. Raw alginate as the control treatment was heated at 140oC in a laboratory oven for different time courses 1.5, 4.5, and 7.5 hours. The assessment of molecular weight, UV-visible and FT-IR spectroscopic studies were applied. By heat treatment, molecular weight of polymer was decreased in a time-dependent manner, though there is no significant difference between 4.5 h and 7.5 h samples. The UV-visible spectroscopic studies pointed that there was a new absorption band between 250 and 290 nm in alginate heated treatments. The higher antiradical scavenging activity were reached from 1.5 h and 4.5 h treatments (19.83% and 20.07%). Interestingly, the antiradical scavenging activity of the longest heating treatment (7.5 h) was reduced (16.85%), similar to the raw alginate (17.89%). Prolonged heat treatments influenced the antioxidant activity and reduced the ability of donate electrons or hydrogen atoms to inactivate this radical action.